Genetic tansformation of Hevea brasiliensis with hman arial ntriuretic Factor - Sunderasan E; Arokiaraj P; Azharuddin Azlina; Badaruddin EBadrul (Journal of Rubber Research, 2012)
Agrobacterium mediated genetic transformation was performed on anther callus of Hevea cultivar GLI with a gene encoding human atrial natriuretic factor (HANF), a peptide hormone that is involved in regulating cardiac blood pressure. The gene constructs containing four different lengths of the indigenous hevein promoter, also incorporated the marker nptII for selection of transformants. Thus far 28 plants were regenerated and their bud-grafted generations were successfully transferred to the soil; all transcript in leaf samples was detected by RT-PCR in a number of original transformants and their vegetative generations, and the authenticity of the amplicon was confirmed by nucleotide sequencing. Polyclonal anti-atrial natriuretic peptide detected a band in the low molecular weigh region in western- immunoblot of leave protein of an original transformed plant, while MALDITOF-TOF and database searches of the corresponding protein band on SDS-gel revealed matches to atrial natriuretic peptide in the C-terminus of HANF.
Keywords: genetic transformation; Hevea brasiliensis; human atrial natriuretic factor; protein mass-spectra analysis; RT-PCR